Various Digestion Protocols Within Microplastic Sample Processing—Evaluating the Resistance of Different Synthetic Polymers and the Efficiency of Biogenic Organic Matter Destruction - Pfeiffer, Felix; Fischer, Elke Kerstin (Frontiers in Environmental Science, 2020)
The digestion of biogenic organic matter is an essential step of sample preparation within microplastic analyses. Organic residues hamper the separation of polymer particles especially within density separation or polymer identification via spectroscopic and staining methods. Therefore, a concise literature survey has been undertaken to identify the most commonly applied digestion protocols with a special focus on water and sediments samples. The selected protocols comprise different solutions, concentrations and reaction temperatures. Within this study we tested acids (nitric acid and hydrochloric acid), bases (sodium hydroxide and potassium hydroxide) and oxidizing agents (hydrogen peroxide, sodium hypochlorite and Fenton’s reagent (hydrogen peroxide 30 % in combination with iron(II)sulfate 0.27 %)) at different concentrations, temperature levels and reaction times on their efficiency of biogenic organic matter destruction and the resistance of different synthetic polymers against the applied digestion protocols. Tests were carried out in three parallels on organic material (soft tissue, hard tissue and calcareous material) and six polymers (low-density polyethylene, high-density polyethylene, polypropylene, polyamide, polystyrene and polyethylene terephthalate) in two size categories. The efficiency of organic matter destruction is highly variable. Calcareous shells showed no to very low reaction to oxidizing agents and bases, but were efficiently dissolved with both tested acids at all concentrations and at all temperatures. Soft and hard tissue were most efficiently destroyed by sodium hypochlorite. However, the other reagents can also have good effects, especially by increasing the temperature to 40-50 °C. The additional temperature increase to 60-70 °C showed a further but less effective improvement, compared to the initial temperature increase. The resistance of tested polymer types can be rated as good except for polyamide and polyethylene terephthalate. Increasing the concentrations and temperatures, however, results in accelerated degradation of all polymers. This is most evident for polyamide and polyethylene terephthalate, which show losses in weight between 15 to 100 % when the digestion temperature is increased. As a concluding recommendation the selection of the appropriate digestion method should be specifically tested depending on the composition of the sample matrix and the project objectives.